Satisfacción del cliente en la agencia principal de Inversiones La Cruz de la ciudad de Iquitos, 2021 - Linares Rojas, Juanita Deivi (2022)
In the study presented, its objective was to identify the level of customer satisfaction in the main agency of Inversiones la Cruz of the city of Iquitos, 2022. Taking for an applied type of research, descriptive level and non-experimental design, since the survey was used as a technique and the questionnaire as an instrument. Concluding that, customer satisfaction is regular; since there are some shortcomings in the dimensions evaluated. Regarding the tangibility dimension, it is regular, because the financial institution has the same modern and well-equipped facilities as expected; as for the reliability dimension, it is regular, since what is advertised by the financial institution is the same as expected; likewise, the safety dimension is regular, because employees as expected show willingness to always help; also in the dimension responsiveness is regular because the same as expected the financial institution provides personalized attention, finally in the dimension empathy of the staff is low, because the financial institution is less than expected on the needs of the client.